2015
DOI: 10.1038/ni.3258
|View full text |Cite|
|
Sign up to set email alerts
|

K33-linked polyubiquitination of Zap70 by Nrdp1 controls CD8+ T cell activation

Abstract: The key molecular mechanisms that control signaling via T cell antigen receptors (TCRs) remain to be fully elucidated. Here we found that Nrdp1, a ring finger-type E3 ligase, mediated Lys33 (K33)-linked polyubiquitination of the signaling kinase Zap70 and promoted the dephosphorylation of Zap70 by the acidic phosphatase-like proteins Sts1 and Sts2 and thereby terminated early TCR signaling in CD8(+) T cells. Nrdp1 deficiency significantly promoted the activation of naive CD8(+) T cells but not that of naive CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 49 publications
4
90
1
Order By: Relevance
“…Because dysregulation of these pathways impairs homoeostasis and immune responses, and can lead to lymphoma or autoimmunity, they are tightly regulated at multiple levels. E3 ligase-mediated ubiquitination is one of these essential regulatory mechanisms3456. TCR signalling and peripheral T-cell tolerance are known to be modulated via the ubiquitination of upstream elements, including TCRζ by Itch7, ZAP70 by the Cbl family and Nrdp1 (ref.…”
mentioning
confidence: 99%
“…Because dysregulation of these pathways impairs homoeostasis and immune responses, and can lead to lymphoma or autoimmunity, they are tightly regulated at multiple levels. E3 ligase-mediated ubiquitination is one of these essential regulatory mechanisms3456. TCR signalling and peripheral T-cell tolerance are known to be modulated via the ubiquitination of upstream elements, including TCRζ by Itch7, ZAP70 by the Cbl family and Nrdp1 (ref.…”
mentioning
confidence: 99%
“…The molecular explanation(s) for the differences in degranulation by CD4 and CD8 T EM are unknown but experiments to determine this difference are an area of active investigation. One potential explanation could be a difference in the strength and/or duration of TCR signaling; it was recently shown that TCR-induced P-ZAP70 in mouse CD8 T cells is completely dephosphorylated within 30 minutes 30 . However, our assessment of the extent of ZAP70 phosphorylation suggests that the difference in degranulation between human CD4 and CD8 T EM interacting with antigen presented by EC cannot be explained by differences in the quantitative strength or duration of signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies and others have demonstrated that Nrdp1 plays a crucial role in cardiac myocardial and neuronal response to ischemic or immune stimuli [11,12,18,19]. Accumulating evidence indicates that Nrdp1-dependent proteolysis of its substrates, such as ErbB3, BRUCE, MyD88, Parkin, eIF3-f, and Clec16a, could constitute the important events to regulate cell growth, inflammation, and tumor genesis [9,11,15,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Nrdp1 has ubiquitin ligase activity and targets proteins such as ErbB3, BRUCE/apollon, Parkin, MyD88, and Zap70 for ubiquitin-mediated degradation [8,9,10,11,12]. Nrdp1 has been reported to be involved in cell growth, tumor suppression, inflammation response, and immune regulation through controlling targeted protein levels [12,13,14,15,16,17]. We have previously shown that the overexpression of Nrdp1 in the heart tissue induced rapid inactivation of cardiac ErbB3 and exacerbated myocardial apoptosis, inflammation, and tissue infarction in a rat model of heart ischemia/reperfusion injury [18].…”
Section: Introductionmentioning
confidence: 99%